2022
DOI: 10.21203/rs.3.rs-1844818/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A nomogram for predicting postoperative overall survival of patients with lung squamous cell carcinoma: a SEER-based study

Abstract: Background Lung squamous cell carcinoma (LSCC) is a common subtype of non-small cell lung cancer. Our study aimed to construct and validate a nomogram for predicting overall survival (OS) for postoperative LSCC patients. Methods A total of 8,078 patients eligible for recruitment between 2010 and 2015 were selected from the Surveillance, Epidemiology and End Results database. The study outcomes were 1-, 2-, and 3-year OS. Analyses performed included univariable and multivariable Cox regression, receiver the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…There is a large difference in OS between N 0 and N 1 stages, and among the T 1 -T 4 stages, T 3 , and T 4 stages have the largest difference in OS, while T 2 and T 3 have the smallest difference. 21 In comparison to other types of lung cancer, T, N, and M staging each had a different impact on OS in patients with LCNEC. In this study, we found that the T stage had no significant influence on OS in the TNM stage of LCNEC patients, while the N and M stages (bone, lung, and brain metastases) were independent influences on OS.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…There is a large difference in OS between N 0 and N 1 stages, and among the T 1 -T 4 stages, T 3 , and T 4 stages have the largest difference in OS, while T 2 and T 3 have the smallest difference. 21 In comparison to other types of lung cancer, T, N, and M staging each had a different impact on OS in patients with LCNEC. In this study, we found that the T stage had no significant influence on OS in the TNM stage of LCNEC patients, while the N and M stages (bone, lung, and brain metastases) were independent influences on OS.…”
Section: Discussionmentioning
confidence: 92%
“…Squamous carcinoma, a common NSCLC, also has T‐staging and N‐staging as independent influences. There is a large difference in OS between N 0 and N 1 stages, and among the T 1 ‐T 4 stages, T 3 , and T 4 stages have the largest difference in OS, while T 2 and T 3 have the smallest difference 21 . In comparison to other types of lung cancer, T, N, and M staging each had a different impact on OS in patients with LCNEC.…”
Section: Discussionmentioning
confidence: 94%